THE IMPACT OF INSTAGRAM SOCIAL MEDIA ON KOPI KENANGAN BRAND LOYALTY - Felix Kenneth Sebastian; Sam’un Jaja Raharja; Mohammad Benny Alexandri (Journal of Management Small and Medium Enterprises (SMEs), 2025)
With the widespread use of social media, companies create various creative content to attract people's attention. One of them is Kopi Kenangan. This research aims to determine the influence of Instagram social media on Kopi Kenangan brand loyalty by studying consumers in the city of Bandung. The method used in this research is quantitative with a descriptive nature and uses a questionnaire as a data collection tool. The sample used was a purposive sampling technique aimed at Kopi Kenangan consumers in Bandung City with a total of 106 respondents. Data analysis was carried out using simple linear regression, coefficient of determination, and hypothesis testing. Based on the research results, the social media Instagram account @kopikenangan.id has an influence on the brand loyalty of Kopi Kenangan consumers. The coefficient of determination value was 30.8%, which shows that the remaining 69.2% is explained by other variables. Keywords: Social Media; Instagram; Coffee Shop; Brand Loyalty